Property Rights, Management Plansand Dynamics of Sustainability in the Coastal Kerala - A. Damodaran (2003)
Environment management plans for coastal zone areas need to be sensitive to the dynamics of property right regimes. With reference to empirical evidence from the coastal zone of Kannur District in Kerala, this paper highlights the necessity of addressing the complexities of property rights for ensuring sustainable management of coastal zones. The paper describes how changing property rights over virtual commons in the study area has led to the disappearance of breeding centres for sardines, pomfrets and mackerel in the study area. The paper explains how Kerala's Coastal Zone Management Plan meant for sustainable development of coastal areas, cannot achieve its stated purpose if it disregards community property rights. The paper further brings out why concepts such as `social cost-benefit analysis' and `safe minimum standards approach' are not adequate tools for analysing the situation in the study area